Creación artistica en la adolescencia: vinculaciones terapéuticas - Rigo Vanrell, Catalina (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
This paper offers a personal point of view about application of new approaches of contemporary artistic creation to learning, practice and artistic experimentation, either in classroom or in specific artherapy whorkshops, that are more adapted for adolescence and youth. All the groups need and use art as a warrant of identity, change and continuity and to hold their cultural values.
Keywords: Art; Artistic techniques; New approaches; Artherapy; Adolescence; Youth; Image; Reality